PRINSIP KEWAJIBAN MINIMUM CORE DAN IMPLEMENTASINYA DALAM PENGELOLAAN KEUANGAN DAERAH DI INDONESIA - Abdurrahim Abdurrahim (Maleo Law Journal, 2021)
The Obligation Core Principles of Minimum Obligation are the answer to the challenges faced by the government / local government regarding the fulfillment of economic, social and cultural rights. The Principle of Minimum Obligation Core functions as a guarantor for the basic needs of the people and as a first step for local governments in carrying out the progressive obligations that have been required by the Covenant, Ecosoc The lack of budgets for fulfillment of the ESC rights in the regions has made the author propose that the Minimum Principles of Core Obligations be used as law in the management of regional finances in Indonesia. In the research, the writer uses normative legal science research with a conceptual approach and legislation, and stratifies the areas that are the target of the author; that is; Bangka Belitung Islands Province, South Kalimantan Province, Denpasar City, Malang City and Palu City. In this study, the authors focus on the right to, especially the rights to education, health, housing and food.Keywords; ESC Rights, Minimum Core Obligation, Regional Budget, Indonesia.